2022
DOI: 10.1159/000524003
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Weekly Lonapegsomatropin from Daily Somatropin in Children with Growth Hormone Deficiency: The fliGHt Trial

Abstract: Introduction. The phase 3 fliGHt Trial evaluated the safety and tolerability of once-weekly lonapegsomatropin, a long-acting prodrug, in children with growth hormone deficiency (GHD) who switched from daily somatropin therapy to lonapegsomatropin. Methods. This multicenter, open-label, 26-week phase 3 trial took place at 28 sites across 4 countries (Australia, Canada, New Zealand, and the United States). The trial enrolled 146 children with GHD, 143 of which were previously treated with daily somatropin. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Switching to weekly LAGH from daily rhGH is well tolerated and maintains the known high safety profile of daily rhGH, 33 as shown in a recently published study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Switching to weekly LAGH from daily rhGH is well tolerated and maintains the known high safety profile of daily rhGH, 33 as shown in a recently published study.…”
Section: Discussionmentioning
confidence: 65%
“…Only a low incidence of GHbinding antibodies but no neutralizing antibodies were observed following lonapegsomatropin treatment. 14 Switching to weekly LAGH from daily rhGH is well tolerated and maintains the known high safety profile of daily rhGH, 33 as shown in a recently published study.…”
Section: Discussionmentioning
confidence: 79%
“…Although no published data have emerged on the impact of LAGH on adherence from real-world use, a recently published clinical trial demonstrated that treatment burden, as evaluated by life interference, was significantly reduced when patients were treated with somatrogon once weekly compared to once daily Genotropin, and the overall treatment experience for somatrogon was preferred by patients and caregivers ( 19 ). Another recent study found a preference for LAGH and reduced treatment burden in patients that switched from daily somatropin to weekly lonapegsomatropin ( 20 ). A reduced treatment burden and preference for a LAGH should translate into improved adherence and outcomes in the real world; prospective real-world studies which have recently been initiated will aim to evaluate this ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children receiving lonapegsomatropin in the extension portions of the phase III trials have continued to show efficacy and safety (13)(14)(15). After completion of the 12 month pivotal randomized trial comparing lonapegsomatropin to DGH (heiGHt) or completion of the 6 month switch trial (fliGHt), children were able to enroll in the enliGHten extension study.…”
Section: Lonapegsomatropinmentioning
confidence: 99%
“…In the phase III fliGHt switch trial, the average IGF-I obtained five days after lonapegsomatropin injection was +1.6 SDS. For subjects who had IGF-I values ≤2 SDS at entry into the fliGHt trial (already receiving DGH therapy), 31.2% of children had IGF-I values five days after lonapegsomatropin injection >+2 SDS at 26 weeks ( 14 ). In the most recently available data for the enliGHten trial, at 130 weeks children had an average IGF-I value five days after lonapegsomatropin injection of +1.46 SDS ( 15 ).…”
Section: Introductionmentioning
confidence: 99%